Zepto precision pulse capsulotomy: A new automated and disposable capsulotomy technology - David F Chang (Indian Journal of Ophthalmology, 2017)
Despite the appeal of an automated method of creating a perfectly circular anterior capsulotomy, global adoption of femtosecond laser capsulotomy (FSLC) has been limited by its high acquisition and per case cost. In addition, the femtosecond laser's large size and the need for eye docking create surgical efficiency and workflow challenges. The Zepto precision pulse capsulotomy (PPC) technology creates a circular anterior capsulotomy of a precise diameter using a disposable handpiece and tip that are used in the normal surgical sequence. Extensive preclinical and clinical testing has resulted in the US Food and Drug Administration (FDA) approval of the technology. Zepto PPC holds promise for complicated eyes such as those with intumescent or brunescent lenses, zonulopathy, or small pupils. This paper and the accompanying videos describe and demonstrate the technique and review the published studies.